Money Can't Buy Love But Can It Buy Peace? Evidence from the EU Programme for Peace and Reconciliation - Tilman Brück; Neil T. N. Ferguson (Institute for the Study of Labor (IZA), 2014)
In 1998, the Good Friday Agreement concluded a period of violence in Northern Ireland yet the scars of the conflict remained prevalent in the political landscape. Rival communities remained divided, economic performance was poor and intercommunity tensions frequently manifested. In a bid to reinforce progress towards a peaceful and stable society, over 1bn of public money was spent between 2000 and 2006 on small-scale community and business ventures. Despite the scale of expenditure, however, little rigorous effort has been made to test the success of the programmes. Splitting Northern Ireland into 582 electoral wards, we merge individual-level on perceptions of neighbourhood quality from the British Household Panel Survey with detailed PEACE II accounts. Noting potential selection and omitted variables biases, we implement two-stage random effects models and show that neither level of spending, nor number of projects, in a region is associated with improvements in perceptions of neighbourhood quality.
Keywords: D74; F35; H56; I38; O18; 330; aid intervention; peacebuilding; terrorism; political violence; Northern Ireland; PEACE II; EU Structural Fund; The Troubles